INTERNALIZING THE VALUES OF THE KHOLAFIYAH ISLAMIC BOARDING SCHOOL IN FORMING WASATHIYAH CHARACTER IN SANTRI AT THE NURUL HASAN AND NURUL HUDA ISLAMIC BOARDING SCHOOL SUKOSARI BONDOWOSO - Arifin, Zainul; Fatimah, Siti; Jannah, Rifqohul; Wulandari, Aulia Fidaus; Rahmah, Ainur; Anggraini, Muhai (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to describe and explain the internalization of Kholafiyah Islamic Boarding School values in forming the Wasathiyah character of students at the Nurul Hasan and Nurul Huda Islamic Boarding Schools Sukosari Bondowoso. The research method used is descriptive qualitative with a Multicase Study research type. The determination of this research used purposive sampling techniques, with techniques, interviews, observation and documentation. Using Miles Hubberman data analysis techniques, namely data collection, data reduction, data display, and data verification. For data presentation, the validity of the data is ensured by using data triangulation and source and method triangulation. The results of the research on the Internalization of Kholafiyah Islamic Boarding School Values in Forming the Wasathiyah Character of Santri at the Nurul Hasan and Nurul Huda Islamic Boarding Schools Sukosari Bondowoso illustrate that the instillation of Kholafiyah Islamic Boarding School Values is proven by the existence of an education system that combines the salafiyah system (the yellow book/diniyah study material) and modern ( general education and using a modern infrastructure system) both in terms of Islamic boarding school objectives, teaching materials, learning methods, educational and educational resources, organization and management of Islamic boarding schools, based on the Washatiyah character. The formation of washatiyah character at the Nurul Huda and Nurul Hasan Islamic Boarding School Sukosari Bondowoso is oriented The Kholafiyah Islamic boarding school system hereby implements the cultivation of moral values using the uswatun hasanah model with the character of Islamic boarding school students who can play an active role in forming a generation of students who are balanced and have morals. This is demonstrated by in-depth religious education by showing the character of piety (Piety): in-depth religious education so that moderate leadership is formed, instilling ethical values so that knowledgeable and moral students are formed, learning from practical experience, independence of attitude and discipline, balance between Diniyah, Generaliyyah, technology, information and modernization, have attitudes and values of respect for diversity with skills and independence that foster an attitude of tolerance and openness with a controlled system in accordance with Islamic boarding school quality management.